Correlation Between the NLRP3 Inflammasome and the Prognosis of Patients With LSCC - Xue, Yi; Du, Huai-Dong; Tang, Di; Zhang, Duo; Zhou, Jian; Zhai, Chang-Wen; Yuan, Cun-Cun; Hsueh, Chi-Yao; Li, Sheng-Jie; Heng, Yu; Tao, Lei; Lu, Li-Ming (Frontiers in Oncology, 2019)
Background: NLRP3 inflammasome is an inflammatory mediator. The expression of NLRP3 inflammasome is associated with the development of various tumors and is closely related to the prognosis of tumors. However, the role of NLRP3 inflammasome in laryngeal squamous cell carcinoma (LSCC) remains unclear. This study aim to investigate the influence of NLPR3 inflammasome expression in LSCC, and especially the NLRP3 inflammasome expression level and the prognosis of LSCC after surgery in a Chinese population. Methods: We used quantitative real-time PCR and immunohistochemical (IHC) staining to calculate the mRNA (20 patients, fresh tissue) and protein expression (104 patients, paraffin tissue microarray) levels of the NLRP3 inflammasome (NLRP3/IL-18/IL-1β/ASC/caspase-1), respectively. We also analyzed the relationship between NLRP3 inflammasome expression levels and LSCC cancer tissues compared with adjacent normal tissues and the clinical features of LSCC. Kaplan–Meier survival curves of overall survival (OS) and disease-free survival (DFS) in LSCC patients were compared and analyzed under different expression levels of the NLRP3 inflammasome. Results: Our results indicated that the mRNA expression of the NLRP3 inflammasome was higher in LSCC cancer tissues compared with adjacent normal tissues (p<0.001). The IHC staining score also demonstrated that the expression of the NLRP3 inflammasome was higher than in the adjacent normal tissues (p<0.001). The NLRP3 inflammasome expression also exhibited a close relationship with the clinicopathological characteristics (especially the stage of LSCC) of LSCC. Univariate Cox regression analysis and multivariate Cox regression analysis revealed that both NLRP3 and IL-1β had an increased risk of LSCC progression (p<0.05). The Kaplan–Meier log rank test (OS and DFS) demonstrated that high expression of NLRP3/IL-18/IL-1β/ASC was statistically different than the low expression group (p<0.05) of LSCC patients after surgery. Conclusion: The high expression group of the NLRP3 inflammasome (NLRP3/IL-18/IL-1β/ASC) had a poorer prognosis (OS and DFS) than the low expression group of LSCC patients 5 years after surgery. The NLRP3 inflammasome (NLRP3/IL-18/IL-1β/ASC) may be used as an auxiliary indicator to predict LSCC patient prognosis after surgery.